The Burden of Care and Life Satisfaction of the Turkish Mothers of Children With Cancer - Gulbeyaz Baran (Iran University of Medical Sciences, 2018)
Background: Cancer could be called family-involving disease. The current study aimed at determining the relationship between the burden of care and life satisfaction of the Turkish mothers of children with cancer. Methods: The current descriptive cross-sectional study was conducted on mothers of 194 children with acute lymphoblastic leukemia referred to a chemotherapy polyclinic. Data were collected using a demographic questionnaire, the Zarit Caregiver Burden Scale, and Life Satisfaction Scale, and analyzed with Student's t-test for independent groups, One-way ANOVA, Mann Whitney U test, Kruskal Wallis, and regression tests using SPSS V. 16. Results: Mean age of children was 7.26±3.78 (years), 53.6% were male, and 64.4% were previously enrolled at school but could not continue to study due to illness. A significant difference was observed between the average life satisfaction scale scores and economic status of the mothers (P<0.005). According to Pearson Product Moment Correlation analysis, a statistically significant negative correlation was observed between life satisfaction and caregiver burden scores (P<0.05) (r=-420, P=0.000). Conclusion: Health care team and especially pediatric nurses should help the mothers by providing information about support systems and counseling services available in the community and facilitating the use of these resources to alleviate their stress and increase their life satisfaction.